Les misérables [videorecording (DVD)] - Shankland, Tom; West, Dominic, 1969-; Oyelowo, David; Akhtar, Adeel; Hugo, Victor, 1802-1885 ([publisher not identified], 2019)
Follows Jean Valjean as he spends his life evading capture by Inspector Javert, against the backdrop of post-Napoleonic civil unrest in France.